2019
DOI: 10.3389/fphar.2019.01244
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Thromboxane Biosynthesis in Health and Disease

Abstract: Thromboxane (TX) A2 is a chemically unstable lipid mediator involved in several pathophysiologic processes, including primary hemostasis, atherothrombosis, inflammation, and cancer. In human platelets, TXA2 is the major arachidonic acid derivative via the cyclooxygenase (COX)-1 pathway. Assessment of platelet TXA2 biosynthesis can be performed ex vivo through measurement of serum TXB2, an index of platelet COX-1 activity, as well as in vivo through measurement of urinary enzymatic metabolites, a non-invasive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 88 publications
4
58
0
3
Order By: Relevance
“…TXA2 is the major AA derivative synthesized via the COX-1 pathway [51] . TXA2 can enhance dopamine release and suppress GABAergic transmission by stimulating the TXA2 receptor TXAR2 [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…TXA2 is the major AA derivative synthesized via the COX-1 pathway [51] . TXA2 can enhance dopamine release and suppress GABAergic transmission by stimulating the TXA2 receptor TXAR2 [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that high levels of glutaric acid indicates that the body may be more susceptible to hematological toxicity ( 47 ). Arachidonic acid is a polyunsaturated ω-6 fatty acid that occurs in the phospholipids of cell membranes; it is a precursor molecule during the synthesis of thromboxane A2 ( 48 ). Arachidonic acid generates thromboxane A2 through the thromboxane pathway to cause platelet aggregation, which triggers various cardiovascular diseases ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…11-DH-TXB 2 is the metabolite of TXB 2 , and the plasma level of 11-DH-TXB 2 has been suggested to be an indicator of TXA 2 production in humans. 18 20 Aspirin activity and antiplatelet action can be evaluated by measurement of the end-products of the TXA 2 pathway, such as 11-DH-TXB 2 . The 11-DH-TXB 2 levels also reflect the amount of TXA 2 derived from other sources besides platelets, such as macrophages and monocytes.…”
Section: Discussionmentioning
confidence: 99%